Polysaccharide-Based Packaging Coatings and Films with Phenolic Compounds in Preservation of Fruits and Vegetables—A Review - Junkun Pan; Chengheng Li; Jiechao Liu; Zhonggao Jiao; Qiang Zhang; Zhenzhen Lv; Wenbo Yang; Dalei Chen; Hui Liu (Foods)
Considerable interest has emerged in developing biodegradable food packaging materials derived from polysaccharides. Phenolic compounds serve as natural bioactive substances with a range of functional properties. Various phenolic compounds have been incorporated into polysaccharide-based films and coatings for food packaging, thereby enhancing product shelf life by mitigating quality degradation due to oxidation and microbial growth. This review offers a comprehensive overview of the current state of polysaccharide-based active films and coatings enriched with phenolic compounds for preserving fruits and vegetables. The different approaches for the addition of phenols to polysaccharides-based packaging materials are discussed. The modifications in film properties resulting from incorporating polyphenols are systematically characterized. Then, the application of these composite materials as protectants and intelligent packaging in fruit and vegetables preservation is highlighted. In future, several points, such as the preservative mechanism, safety evaluation, and combination with other techniques along the whole supply chain could be considered to design polyphenol–polysaccharides packaging more in line with actual production needs.